Debunking the myth of high achievers in Finnish primary teacher education: first-year preservice teachers' learning strategies and study success - Vilppu Henna; Mankki Ville; Lähteenmäki Marko; Mikkilä-Erdmann Mirjamaija; Warinowski Anu (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
This study aimed to explore the admitted students of Finnish primary teacher education programmes from the viewpoint of learning strategies, and academic success. An overall view was derived from national register data, which were supplemented with questionnaire data gathered from three teacher education units (N = 216). Primary teacher programmes currently seem to attract and select mediocre secondary school graduates from academic perspective, contrary to previous studies. Furthermore, women enter the programmes with higher exam scores than men and have more success in their studies. Based on their learning strategies, students were divided into subgroups of deep and independent learners, and reproductive and support-dependent learners. Previous study success was positively associated with first-year study success. It is important for teacher educators to acknowledge that the students are rather mediocre in the academic sense, even reproductive and lacking regulation skills, and thus might need support in developing into professional learners.